Preliminary revision of schefflera forst. & Forst. (Araliaceae) in Sarawak - Siti Noor Aishah, Binti Mohd Noor (Universiti Malaysia Sarawak, UNIMAS, 2013)
Preliminary revision of Schefflera in Sarawak was done in Sarawak Herbarium (SAR) of Sarawak Forest Department. All the specimens studied were from dried specimens. There are 357 specimens that have been observed. From the specimens observed, there are 23 Schefflera species found in Sarawak and an additional of 19 unpublished names. This gives a total of 42 Schefflera species of that can be found in Sarawak. A preliminary taxonomic key has been constructed for selected species. Species descriptions of selected species have been carried out. The species selected are S. beccariana, S. borneensis, S. kuchingensis, S. lasiocalyx, S. laxiflora, S. mjoebergii, S. remotiserrata and S. tetandra. From this study, it shows that Schefflera species can be found in wide geographical and elevational distribution.